Analisis Manfaat Dan Tantangan Dalam Implementasi Keamanan Web HTTP Dan HTTPS - Sholah Islamey, Daffa; Muwafi , Muhammad; Anggoro, Musthafa; Fathan Ramadhan, Muhammad; Wijaya, Hasan; Dina Kalifia, Anna (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2024)
The development of internet technology has led to an increased need for data security in web communications. HTTP (Hypertext Transfer Protocol) and HTTPS (Hypertext Transfer Protocol Secure) protocols are the two main protocols used to access information on the web. This article comprehensively discusses the benefits and challenges in implementing HTTPS compared to HTTP, focusing on the aspects of security, performance, and user trust. HTTPS provides significant data encryption to protect sensitive information from cyber threats such as man-in-the-middle attacks and data interception. In addition, the use of HTTPS can improve SEO (Search Engine Optimization) rankings and build user trust through security indications such as the padlock icon in the browser. However, HTTPS implementation also faces challenges, including the need for SSL/TLS certificates, increased server computing load, and potential compatibility issues with legacy systems. Through literature analysis and case studies, this research found that despite the barriers to HTTPS adoption, the benefits gained in terms of security and user trust far outweigh the cost and effort required.